Rice phyllosphere bacteria producing antifungal compounds as biological control agents of blast disease - SRI MARTINA WIRASWATI; ABDJAD ASIH NAWANGSIH; IMAN RUSMANA; Aris Tri Wahyudi (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Wiraswati SM, Nawangsih AA, Rusmana I, Wahyudi AT. 2020. Rice phyllosphere bacteria producing antifungal compounds as biological control agents of blast disease. Biodiversitas 21: 1273-1278. In vitro analysis of rice phyllosphere bacteria can be developed as biocontrol agents of blast disease using their antifungal activity. To prove the efficacy of bacterial isolates in reducing the severity of blast disease, a greenhouse experiment was conducted. Furthermore, antifungal compounds produced by potential bacterial isolate were also identified using Thin Layer Chromatography (TLC) and Liquid Chromatography-Mass Spectrometry/ Mass Spectrometry (LC-MS/MS) analysis. The application of seven rice phyllosphere bacterial isolates significantly reduced the severity of blast disease in rice (var: Ciherang). Surprisingly, the isolate STGG 14 is the most effective with 70.83% of blast disease reduction. Isolate STGG 14 has been identified as Bacillus subtilis subsp. subtilis which is known as various bioactive compounds producer. It was confirmed through identification of antifungal compounds produced by isolate STGG 14. The bioautography test shows that crude bioactive compounds from isolate STGG 14 could inhibit P. oryzae race 173. On the further analysis using LC-MS/MS, four bioactive compounds isolated from isolate STGG 14 were identified as moracin C, psoralen, 4,6-dimethyl-3 (4’-hydroxyphenyl) coumarin and xanthotoxin. All identified compounds except moracin C, belong to the coumarin group. According to the previous studies, among all compounds, psoralen and xanthotoxin displayed antifungal activity against several fungal pathogens.